1991
DOI: 10.1002/jmv.1890330212
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Oka varicella vaccine strain from wild varicella‐zoster virus strains isolated from vaccinees and household contact

Abstract: The Oka varicella vaccine strain can be differentiated from wild-type strains by its unique restriction endonuclease fingerprinting (REFP: HpaI-K and EcoRI-P) pattern of the gpV-coding region of the varicella-zoster virus (VZV) genome. VZV-DNAs from patients with complicated clinical courses related to vaccination were examined to determine whether they were vaccine-derived or wild-type. A virus was isolated from a one year-old boy with acute lymphocytic leukemia (ALL) who developed typical varicella 28 days a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 17 publications
(20 reference statements)
1
19
0
Order By: Relevance
“…In comparison, 19 to 20% of wild-type viruses being positive for BglI site have been found in the United Kingdom and the United States [LaRussa et al, 1992;. The identification of this BglI polymorphism in clinical isolates before the introduction of varicella vaccine indicates that this genetic alteration arose in the United States as the result of a single-base-pair mutation [LaRussa et al, 1992] and has not been created by recombination between vaccine and wild-type virus, which has been observed in vitro [Dohner et al, 1988] and in vivo [Shiraki et al, 1991]. Because of the rare detection of Oka, such recombination is also unlikely in Germany.…”
Section: Discussionmentioning
confidence: 94%
“…In comparison, 19 to 20% of wild-type viruses being positive for BglI site have been found in the United Kingdom and the United States [LaRussa et al, 1992;. The identification of this BglI polymorphism in clinical isolates before the introduction of varicella vaccine indicates that this genetic alteration arose in the United States as the result of a single-base-pair mutation [LaRussa et al, 1992] and has not been created by recombination between vaccine and wild-type virus, which has been observed in vitro [Dohner et al, 1988] and in vivo [Shiraki et al, 1991]. Because of the rare detection of Oka, such recombination is also unlikely in Germany.…”
Section: Discussionmentioning
confidence: 94%
“…This is partly due to a lack of efficient tools necessary for such studies; however, major technological advances in the last decade now allow those types of studies. With respect to VZV, it has been shown that recombination between the live varricella vaccine and wild-type VZV occurs during coinfection in vitro [46] and has been suggested to occur in vivo [47]. Most recently, Breuer and colleagues [39] referred to the emergence of new wild-type/vaccine recombinants by partial-genome sequencing of VZV isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of Isolated DNA Viral DNA was prepared from the nucleocapsid as described previously [Shiraki et al, 1991;Ida et al, 1999;Yoshida et al, 2005] and were subjected to RE fragment comparison. The genital, first whitlow (whitlow 1), and recurrent whitlow (whitlow 2) isolates, five strains of unrelated clinical genital HSV-2 isolates, and the 7401H HSV-1 strain Okuda et al, 2004;Yoshida et al, 2005] were compared for their epidemiological relatedness in the profiles of RE fragments of their DNA after BamHI, BglII, EcoRI, and SalI digestion.…”
Section: Restriction Endonuclease (Re)mentioning
confidence: 99%
“…The genital and two whitlow isolates were identified as HSV-2 by a Microtrack assay and the PCR products of the DNA polymerase region (data not shown). RE fragment polymorphism was used to examine the epidemiological relatedness of the genital, first, and recurrent whitlow isolates by comparison with the other clinical isolates [Buchman et al, 1978[Buchman et al, , 1980Shiraki et al, 1991]. Figure 2 shows the profiles of RE fragments of DNA from the genital and two whitlow isolates as well as HSV strains.…”
Section: Genotypic Characterization Of Genital and Two Whitlow Isolatesmentioning
confidence: 99%